Distribution of added value and cost under sustainability strategies (Costos y Gestión, 2020)
Is the distribution of added value between the stakeholders a cost? Under the traditional view of AssetAccounting in alliance with the Theory of Stockholders, all contingent payback (depending on the results) toan agent other than the shareholder is considered a cost. Through this paper our attempt is to answer thesame question from another perspective, taking into account the following principles/on the basis of thefollowing statements:I. Stakeholders theory with a long-term sustainability view seeking a community of interests (rather thanthe short-term view which confronts the stakeholders in the Theory of Stockholders).II. Ex-ante point of view (rather than the historical ex-post point of view).III. Management accounting under the approach of the General Theory of Costs (rather than AccrualsAccounting).IV. Maximization of added value as the main economic goal (rather than maximization of absolute utility).
Keywords: Management; General Theory of Costs; Enterprise Rsik/Business Risk; Stakeholder; Stockholder; Sustainability; Added Value